IMPLEMENTASI FUNGSI MANAJEMEN DALAM KEGIATAN TAHFIZH DAN QIRAAH SANTRI ASRAMA AL-MADANI MA’HAD AL-ZAYTUN - Rahma Mahmudah; Ahmad Asrof Fitri; Meity Suryandari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the implementation of management functions planning, organizing, actuating, and controlling in the tahfizh (Qur’an memorization) and qiraah (Qur’an recitation) activities of students at Al-Madani Dormitory, Ma’had Al-Zaytun. The research employs a qualitative approach with a field research design. Data were collected through interviews, observations, and documentation, and analyzed using Miles and Huberman’s interactive model, which includes data collection, reduction, presentation, and conclusion. The results show that the implementation of management functions has been carried out properly but is not yet optimal in the actuating and controlling aspects. In planning, the program is well-structured but lacks consideration of individual students’ abilities. The organizational structure is clear, yet interdepartmental coordination still needs improvement. The implementation phase indicates high enthusiasm among students, which declines mid-semester due to monotonous learning methods. Meanwhile, supervision is conducted regularly but focuses more on the quantity of memorization rather than the quality of recitation and understanding of meaning. The study concludes that a collaborative management model supported by digital technology and innovative learning methods is needed to enhance the effectiveness of tahfizh and qiraah programs within Islamic boarding schools. Keywords: Management Functions, Tahfizh, Qiraah, Islamic Education Management, Ma’had Al-Zaytun.